ADVANTAGES AND DISADVANTAGES OF ONLINE EDUCATION PROBLEM AND SOLUTION - Turg`unova, Fazilat; Rustamova Shahnoza Abdurahimovna (Журнал иностранных языков и лингвистики, 2023)
Nowadays many people study online: they take courses, learn about new programs, and even change jobs. Technologies are evolving rapidly, so there is no point in ignoring the opportunities for rapid development. Additionally, these are times of fierce competition, and entrepreneurs are being forced to master new tools and technologies to stay ahead of their competitors. For this reason, distance learning, which will be discussed in this article, is developing rapidly. We won’t talk about the pros and cons of distance learning for students but will look at the pros and cons of online courses for entrepreneurs.